Development of a Strain-Specific Detection and Quantification Method for Bifidobacterium animalis subsp. lactis HN019 Using WGS-SNP Analysis and qPCR - Da Mao; Lei Zhao; Bo Zhao; Hongbin Xu; Qinghe Zhang (Microorganisms, 2025)
Accurate quantification of Bifidobacterium animalis subsp. lactis HN019, a clinically validated probiotic strain conferring immune modulation, gastrointestinal health, and gut barrier integrity benefits, is essential for diverse applications. To address the critical need for strain-specific detection, we developed a quantitative PCR (qPCR) assay targeting a unique single-nucleotide polymorphism (SNP) within the galK gene, identified through comparative whole-genome sequencing (WGS) analysis of 31 B. animalis subsp. lactis strains. The assay exhibited exceptional specificity, distinguishing HN019 from 19 other Bifidobacterium strains. Sensitivity tests indicated a detection limit of 0.5 pg of DNA and 103 CFU/mL of bacterial cells, making it suitable for industrial-scale applications. Additionally, the method exhibited strong repeatability, reproducibility across different qPCR platforms, and resistance to interference from high cell density of B. animalis subsp. lactis DSMZ 10140. Successful quantification of HN019 in complex multi-strain probiotic powders confirmed its practical reliability. This work establishes a rapid, robust, and scalable tool for precise probiotic strain tracking, addressing critical quality control and regulatory compliance needs within the rapidly expanding probiotic industry.